Mapping of Competence and Professionalism Assessment of Open University Tutors - Berlian, Mery; Vebrianto, Rian; Thahir, Musa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
In education, there are still many problems with the performance of employees, school principals, or education providers that are not satisfactory. In a country, quality human resources will provide the welfare of its people. Therefore, improving the welfare of the Indonesian people must be based on the development of quality services and education. This study aims to describe the distribution of tutors, assess their professionalism, and produce policy recommendations for the Open University in general. This type of research is a survey with a research sample of 258 tutors, namely 127 male (49.2%) and 131 female (50.8%). The instrument used is a professionalism questionnaire comprising six constructs with a Cronbach's Alpha value of 0.924. The technique used to analyze the data is quantitative descriptive analysis and inferential statistics. The results showed that there was a significant relationship between income, age, years of service, rank, and professional work status (P<0.05), but there was no relationship between gender and professionalism (P>0.05). This study recommends the need to recruit new tutors considering that many tutors are over 50 years old. There are also some tutors with Bachelor's degrees who need to be upgraded to tutors with Masters or even Doctoral degrees.